Dasar Pertimbangan Hakim Dalam Gugatan Wanprestasi Perjanjian Antara Penggugat Dan Tergugat Terkait Biaya Peningkatan Status Tanah Sporadik Menjadi Sertifikat Hak Milik (Studi Putusan Nomor : 25/Pdt.G/2020/PN.Tjk) - Tami Rusli; Yulia Hesti; Kenny Septhalia (Jurnal Humaniora : Jurnal Ilmu Sosial, Ekonomi dan Hukum, 2022)
Default is the non-fulfillment or failure to carry out the obligations as specified in the agreement made by one of the parties who entered into the agreement. This study discusses the issue of how the judge's considerations and legal consequences in the lawsuit for default of the agreement between the Plaintiff and the Defendant related to the cost of increasing sporadic land status based on Decision Number: 25/Pdt.G/2020/PN.Tjk. This study uses a normative juridical approach and an empirical juridical approach. Collecting data by field studies and literature studies. Data analysis was carried out in a qualitative juridical manner, namely the analysis was carried out descriptively. The Panel of Judges in providing legal considerations in default cases must be careful and thorough, if wrong in providing legal considerations it will harm the litigants to obtain legal certainty and a sense of justice based on the judge's decision, thereby minimizing the possibility of disputes due to defaults that are done wrongly. one party.